Electric vehicle communities for electric market - Ferreira, João C. (2011)
In this work is proposed the design of a system to create and handle an Electric Vehicle (EV) community, based on social networks collaborative approach and a credit mechanism to incentive participation and mechanism to incentive participation and divide profits. This system is part of a V2G (Vehicle-to-Grid) module that allows EV owners to be aggregated in communities and participate in the electricity market. With this system it is possible for the EV owners to win money while the EVs are parked and plugged, delivering back to the electrical grid part of the energy stored in the batteries, increasing the attractiveness of EVs.